Design of gen-z meditation center in Batam with zen architecture concept - Amien, Ilham; Arif, Akbar Rifai; Saragih, Yohanes Kristy; Maulana, Indri Astuti (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Generation Z, known as the digital generation, faces unique psychological challenges, mainly related to high levels of stress and anxiety, influenced by intense academic competition and work pressures. Addiction to gadgets and social media also contributes to sleep disorders and social isolation. Meditation has been shown to be effective in reducing stress levels in Generation Z. Therefore, the design of a meditation centre in Batam City using the Zen architectural concept can be an important step in supporting the mental health of this generation. The Zen architectural concept was chosen for its simplicity, which is in line with the need for meditation and tranquility that Generation Z seeks. By providing inclusive meditation spaces, Batam City can expand its spiritual outlook and support the overall mental health of its people. Therefore, this research concludes that designing a Gen-Z meditation centre in Batam City using the concept of Zen architecture is a step towards addressing the mental health challenges of this generation.